Hereditary leiomyomatosis and renal cell cancer (HLRCC), pheochromocytoma (PCC)/paraganglioma (PGL) and germline fumarate hydratase (FH) variants - John J Orrego; Joseph A Chorny (Endocrinology, Diabetes & Metabolism Case Reports)
Hereditary leiomyomatosis and renal cell cancer (HLRCC) is an autosomal dominant condition characterized by multiple cutaneous and uterine leiomyomas and renal cell cancer (RCC). HLRCC is caused by germline pathogenic/likely pathogenic (P/LP) variants in the fumarate hydratase (FH) gene on chromosome 1q42.3, encoding the mitochondrial enzyme responsible for the conversion of fumarate to malate in the Krebs cycle. 0.6–3.1% of individuals with pheochromocytoma/paraganglioma (PCC/PGL) carry a germline variant in the FH gene. Most of these patients have no personal or family history of HLRCC-associated manifestations, but some of them do. We described a female-to-male transgender with HLRCC who presented with large symptomatic uterine leiomyomas in the third decade of life and was diagnosed with a PCC 19 years after hysterectomy and with cutaneous leiomyomas and an aggressive form of RCC in the sixth decade of life. With the publication of this case and the review of the existent literature, and until more information becomes available, we would like to emphasize that clinicians should be aware of the possible connection between HLRCC and PCC/PGL, that genetic testing for susceptibly genes for PCC/PGL should include the FH gene and finally that patients with HLRCC should be screened for PCC/PGL.